(untitled) (Research, Society and Development, 2022)
Objective: to identify nurses’ perceptions of pain assessment and which non-pharmacological measures are used before painful procedures in the Conventional Intermediate Care Unit. Methodology: Qualitative, descriptive and exploratory study, carried out between September and October 2017, with nurses working in the Conventional Intermediate Care Unit. Data were collected through an interview script and the analysis of the speeches in the interviews was done through Content Analysis. Results: Five nurses participated, with professional experience ranging from one to six years, two nurses aged 04 years and one with 06 years, all had specialization. Two thematic categories emerged: “Perception of pain by professionals”; “Pain Relief Measures”. Final considerations: It was possible to identify the nurses’ perception of pain assessment and the non-pharmacological measures they routinely use before performing painful procedures at the NICU. It is noticed that nurses are sensitive to the cause of pain in the NB, as through their reports they are able to recognize that the newborn feels pain not only when undergoing painful procedures, but also when faced with a change of position. However, they added that environmental changes at UCINCo, through noise and lighting, are stressors and bring discomfort.